2018
DOI: 10.1037/neu0000441
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining prospective memory functioning in amnestic mild cognitive impairment: A lifespan approach to the critical role of encoding.

Abstract: Objective: Prospective memory (PM), the ability to remember to perform future activities, is a fundamental requirement for independent living. PM tasks pervade throughout our daily lives and PM failures represent one of the most prominent memory concerns across the entire lifespan. This study aimed to address this issue by exploring the potential benefits of specific encoding strategies on memory for intentions across healthy adulthood and in the early stages of cognitive impairment. Method: PM performance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Previous studies have reported age-related PM decline in healthy older adults (Ball et al, 2019 ; Gonneaud et al, 2017 ; Lamichhane et al, 2018 ), which supports the association between ageing and PM decline. In the included studies, the clinical populations demonstrated a significantly poorer PM performance than the healthy populations (Kinsella et al, 2016 ; Lee et al, 2016 ; Mateos et al, 2016 ; Ozgis et al, 2009 ; Pereira et al, 2015 , 2018 ; Shelton et al, 2016 ), which supports a deficit in PM. The positive training effect found for the healthy and clinical older populations may reflect an improvement in PM in the training group compared with the control group.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies have reported age-related PM decline in healthy older adults (Ball et al, 2019 ; Gonneaud et al, 2017 ; Lamichhane et al, 2018 ), which supports the association between ageing and PM decline. In the included studies, the clinical populations demonstrated a significantly poorer PM performance than the healthy populations (Kinsella et al, 2016 ; Lee et al, 2016 ; Mateos et al, 2016 ; Ozgis et al, 2009 ; Pereira et al, 2015 , 2018 ; Shelton et al, 2016 ), which supports a deficit in PM. The positive training effect found for the healthy and clinical older populations may reflect an improvement in PM in the training group compared with the control group.…”
Section: Discussionmentioning
confidence: 81%
“…After excluding these studies, we had 2,672 participants across 42 studies with enough details to calculate the average demographic statistics (weighted M age = 72.01 years, SD = 6.45, range = 50–94). 3 An additional 12 studies did not report sufficient data for calculating the number of participants in the training and control conditions separately 4 (Altgassen et al, 2015 ; Kinsella et al, 2016 ; Lee et al, 2013 ; McDougall, 2000 ; McFarland & Glisky, 2011 ; Niedźwieńska et al, 2014 ; Pereira et al, 2012 , 2015 , 2018 ; Schnitzspahn & Kliegel, 2009 ; Villa & Abeles, 2000 ; Zimmermann & Meier, 2010 ). As a result, the remaining 30 included studies 5 had 993 participants (weighted M age = 72.13 years, SD = 6.44, range = 50–93) in the training condition and 698 participants (weighted M age = 71.48 years, SD = 6.42, range = 50–94) in the control condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was based on an a priori power analysis using the GPOWER 3 software. The effect size f was based on previous research ( Pereira et al, 2018 ). The alpha level was 0.05, power was 0.95, and an effect size of 0.5 was considered.…”
Section: Methodsmentioning
confidence: 99%
“…For encoding, these previous studies (e.g., Ball and Bugg, 2018 ) showed a “specific advantage”, indicating that the memory content comprised mostly specific events with a high proportion of specific memories; to recall this content, there was an advantage to remembering specific details ( Chen, 2013 ). Furthermore, Scullin et al (2018) systematically investigated the encoding process for ProM and confirmed that specific was better than non-specific cue encoding, for which 22.5% of participants gave little thought to the ProM tasks and tended to translate categories to specific exemplars ( Pereira et al, 2018 ). It may be that participants using non-specific cue encoding had to pay closer attention than those using specific cue encoding to correctly determine ProM targets.…”
Section: Introductionmentioning
confidence: 94%